PSIKOEDUKASI DUKUNGAN PSIKOLOGIS AWAL (DPA) PADA KONSELOR TEMAN SEBAYA - Hendriati, Nata; Iswinarti, Iswinarti (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Psychological First Aid (PFA) is a series of basic skills that aim to reduce the negative impact of stress and prevent the emergence of worse mental health disorders due to disasters or critical situations. PFA psychoeducation is expected to increase participants' knowledge and understanding of appropriate psychosocial responses to traumatic events and how to provide support to individuals facing difficulties. Peer support groups or peer support, as the first people asked to assist peers who experience a crisis incident at school, are considered to need to receive psychoeducation regarding PFA. PFA psychoeducation for peer support was given for 3 hours at school, then continued by measuring peer support's knowledge and understanding of the principles of psychosocial support using a questionnaire. 16 peer counsellors participated in psychoeducation activities, consisting of 8 men and 8 women. The results of post-tests, observations and interviews showed that participants were quite happy in participating in psychoeducational activities. Students know PFA services and understand the steps for providing PFA. Some research limitations and obstacles experienced by researchers can be of concern and become lessons for future researchers.